Assessing the potential of ultraviolet irradiation for inactivating waterborne fungal spores: kinetics and photoreactivation studies - Duque-Sarango, Paola; Delgado-Armijos, Nicole; Romero-Martínez, Leonardo; Pinos-Vélez, Verónica (Frontiers in Environmental Science, 2023)
Ultraviolet disinfection has been extensively studied in recent years, especially in bacteria; however, there are still insufficient studies in fungal spores. Moreover, most studies use static batch reactors instead of continuous flow reactors, which are used mainly at the industrial scale. In the present work, the inactivation and reactivation characteristics of two species of filamentous fungi were studied using a single-pass flow-through UV-C reactor (FTR). For this purpose, Aspergillus niger and Penicillium sp. spores were suspended in water and circulated through the reactor at different UV-C doses. The effects on inactivation and reactivation after 24 in either light or dark conditions were studied. The two fungal strains studied show different UV-C treatment resistance and damage repair capacity. With the experimented FTR system, an inactivation efficiency of up to 2 log units (99% removal) was achieved with doses of 220.1 ± 24.3 mJ cm −2 in the case of A. niger and 123.8 ± 6.3 mJ cm −2 in the case of Penicillium sp. The effect of dark repair is negligible, while the photoreactivation process is relevant in the case of Penicillium sp., since D2 increased by 53.8 % just after UV-C exposure due to photoreactivation. In general, A. niger is more UV-C resistant than Penicillium sp.; however, the latter has a greater capacity to photoreactivate.